Owls Clever Survivors - Mikkola, Heimo (IntechOpen, 2023)
Owls are one of the most fascinating bird families. They have inspired much folklore and superstition worldwide. This book discusses this nocturnal species and their unique physiology and anatomy. It includes owl studies from countries including Bulgaria, Ecuador, Iraq, Slovakia, Syria, and Africa.